2019
DOI: 10.1111/hiv.12797
|View full text |Cite
|
Sign up to set email alerts
|

Post‐exposure prophylaxis for HIV infection in sexual assault victims

Abstract: ObjectivesSexual assault (SA) is recognized as a public health problem of epidemic proportions. Guidelines recommend the administration of post‐exposure prophylaxis (PEP) after an SA. However, few data are available about the feasibility of this strategy, and this study was conducted to assess this.MethodsWe conducted a retrospective, longitudinal, observational study in SA victims attending the Hospital Clinic in Barcelona from 2006 to 2015. A total of 1695 SA victims attended the emergency room (ER), of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Feeling sick-experienced. Our study supports prior research that HIV PEP side effects were reported by all who initiated HIV PEP and acted as a driving force when participants decided to discontinue the medications (Abrahams & Jewkes, 2010;Inciarte et al, 2020;Krause et al, 2014;Vetten & Haffejee, 2005, 2008. Loutfy et al (2008) found 82% of patients stopped HIV PEP because of side effects; followed by interference with daily routine (42%); and not being able to miss work or school (22%).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Feeling sick-experienced. Our study supports prior research that HIV PEP side effects were reported by all who initiated HIV PEP and acted as a driving force when participants decided to discontinue the medications (Abrahams & Jewkes, 2010;Inciarte et al, 2020;Krause et al, 2014;Vetten & Haffejee, 2005, 2008. Loutfy et al (2008) found 82% of patients stopped HIV PEP because of side effects; followed by interference with daily routine (42%); and not being able to miss work or school (22%).…”
Section: Discussionsupporting
confidence: 89%
“…Fear of HIV has been reported by patients as both positively and negatively impacting HIV PEP continuance (Vetten & Haffejee, 2005, 2008. Reported barriers to HIV PEP completion include medication side effects (Garcia et al, 2005;Inciarte et al, 2020;Krause et al, 2014;Vetten & Haffejee, 2005, 2008 and financial barriers (Diniz et al, 2007;Malinverni et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If PEP is offered, the following information should be discussed with the survivor: the necessity of early initiation of PEP to optimize potential benefits (i.e., as soon as possible after and <72 hours after the assault), the importance of close follow-up, the benefit of adherence to recommended dosing, and potential adverse effects of antiretroviral medications. Providers should emphasize that severe adverse effects are rare from PEP ( 1431 1435 ). Clinical management of the survivor should be implemented according to the HIV PEP guidelines and in collaboration with specialists ( 1436 ).…”
Section: Sexual Assault and Abuse And Stismentioning
confidence: 99%
“…Although PEP management of occupational and non-occupational exposure is similar, appropriate medical treatment for sexual assault patients is complex. Compliance with medication adherence and recommended nPEP follow-up is poor in this patient population [13]. This suggests that there may be a need for a standardized, systematic approach to patient treatment; however, data regarding the efficacy or impact of ED nPEP protocols are scarce, in particular standardized electronic medical record (EMR) order sets.…”
Section: Introductionmentioning
confidence: 99%